Relationships between team characteristics and soldiers’ organizational commitment and well-being: the mediating role of psychological resilience - Kanapeckaitė, Rosita; Bagdžiūnienė, Dalia (Frontiers in Psychology, 2024)
Background Military operations call for a great deal of readiness and resilience on the part of the soldiers, once confronted with high-stress scenarios. Resilience, in this context, has to do with the ability to effectively cope with the adverse impacts of setbacks and the accompanying stressors, ensuring that overall performance and combat effectiveness remain unhampered. In the modern military context, it is relevant to examine more deeply the phenomenon of soldiers’ resilience, its importance in positive organizational and personal outcomes as well as the role of team factors for the improving of soldiers’ resilience. The study aimed to examine team-level factors that determine soldiers’ psychological resilience and to reveal the mediating role of resilience in the relationships between team factors and organizational commitment and well-being. Sample A cross-sectional convenience sample included 422 soldiers on professional military duty in the Lithuanian Armed Forces. Methods Data were collected using self-administered questionnaire. We applied structural equation modeling to assess the research models. Results Team cohesion and colleague support proved to be reliable predictors of increased psychological resilience; individuals with higher resilience were more committed to the organization and experienced higher well-being; the results confirmed the hypotheses that soldier resilience has a mediating effect on the relationships between team characteristics and their commitment, and well-being. Conclusion The findings help clarify the relationships between team characteristics, soldiers’ resilience, commitment and well-being. They may be useful for improving soldier resilience through team cohesion, mutual support, cooperation, and for integrating team-building interventions into military resilience training programs.